And now what? a guide to leadership and taking charge in your new role - Stein, Guido 1963- (Emerald Publishing, 2018)
When you start a new managerial role, there is an inevitable contrast between what you believed you would find and what you're actually faced with. And Now What? helps you manage this gap between expectation and reality, ensuring that you get off to the best possible start in your new job